Relationship Between Self-Esteem and Problematic Social Media Use Amongst Chinese College Students: A Longitudinal Study - Wang H (Psychology Research and Behavior Management, 2024)
Hui Wang Xiamen University Tan Kah Kee College, Zhangzhou, 363105, People’s Republic of ChinaCorrespondence: Hui Wang, Email monkeykinghui@163.comPurpose: Numerous cross-sectional investigations have delved into the association between the self-esteem of college students and problematic social media use (PSMU). Nevertheless, the debated causal sequence between the two factors persists, and their unclear developmental connection over time prevails.Methods: We used a questionnaire method to follow 321 students in Chinese college over a period of 18 months and three times, of which 137 are male and 184 are female, with an average age of 18.42 years (SD = 0.78) at time 1. Descriptive statistics were used to present the general characteristics of the study participants. Moreover, the latent growth model was used to explore the developmental trajectory of self-esteem and PSMU and to explore the interplay between the two factors from a developmental perspective. On this basis, a cross-lagged model was used to verify the causal relationship between self-esteem and PSMU.Results: In China, (a) the self-esteem levels of college students continuously decline during their academic years, whilst PSMU levels steadily increase. (b) The self-esteem of Chinese college students significantly negatively predicts PSMU. (c) The initial level of self-esteem amongst Chinese college students can significantly negatively predict the initial level of PSMU. Additionally, the rate of decline in self-esteem amongst Chinese college students can negatively predict the rate of increase in PSMU.Conclusion: Obtained results serve as a valuable resource for researchers and educators, enabling strategic intervention in addressing issues related to PSMU amongst college students from a developmental perspective.Keywords: self-esteem, problematic social media use, latent growth model, cross-lagged model, longitudinal study